Training the Trainer: Measuring the Long-Term Effectiveness of AI Upskilling Programs for Indonesian Educators - Elok Nur Affah Al Akromi (Al-Makki Publisher, 2025)
Indonesia's national artificial intelligence (AI) education roadmap (2025–2045) positions teacher AI competency as foundational to its Golden Generation vision, yet the long-term effectiveness of AI upskilling programs for Indonesian educators remains empirically unexamined. This study aims to evaluate the extent to which AI-related competencies are retained over time, identify key factors influencing sustained AI integration among teachers, and compare the effectiveness of different upskilling programs across regional contexts. This longitudinal mixed-methods study measured the durability of AI competency gains among 347 in-service K–12 teachers across urban, peri-urban, and remote regional strata over four measurement waves: pre-intervention, immediate post-intervention, six-month follow-up, and twelve-month follow-up. Participants were drawn from two nationally deployed AI upskilling programs Platform Merdeka Mengajar (PMM) and Microsoft Elevate and assessed using a validated four-subscale questionnaire, semi-structured interviews, and structured classroom observation checklists. Results revealed a consistent